Shaping science and technology policy : the next generation of research - Guston, David H.; Sarewitz, Daniel R. (Science and technology in society, 2006)
With scientific progress occurring at a breathtaking pace, science and technology policy has never been more important than it is today. Yet there is a very real lack of public discourse about policy-making, and government involvement in science remains shrouded in both mystery and misunderstanding. Who is making choices about technology policy, and who stands to win or lose from these choices? What criteria are being used to make decisions and why? Does government involvement help or hinder scientific research? Shaping Science and Technology Policy brings together an exciting and diverse group of emerging scholars, both practitioners and academic experts, to investigate current issues in science and technology policy. Essays explore such topics as globalization, the shifting boundary between public and private, informed consent in human participation in scientific research, intellectual property and university science, and the distribution of the costs and benefits of research. Contributors: Charlotte Augst, Grant Black, Mark Brown, Kevin Elliott, Patrick Feng, Pamela M. Franklin, Carolyn Gideon, Tené N. Hamilton, Brian A. Jackson, Shobita Parthasarathy, Jason W. Patton, A. Abigail Payne, Bhaven Sampat, Christian Sandvig, Sheryl Winston Smith, Michael Whong-Barr